cercospora Needle Blight: a Potential Threat to Indigenous Pines in India - Singh, Sujan (Indian Forester, 1982)
Cercospora needle blight hither-to reported on pine seedlings in nursery stage, is now recorded on two indigenous pines, Pinus roxburghil and Pinus wallichiana on natural regeneration and in plantations. All the four species of exotic pines namely P. caribaea, P. patula, P. elliotti and P. greggii which are being raised extensively in plantations were found to develop resistance against attack of Cercospora needle blight in plantations though they were severely attacked by the disease in nurseries. The pathogen is of exotic origin and is an inadvertent introductioniInto the country. It is still localized to areas where exotic pines have been raised. Measures are suggested to eradicate the causal fungus, Cercoseptoria pini-densiflorac, from the infected nurseries at this stage as such eradication may become difficult when the fungus establishes itself in natural zones of P. roxburghii and P. wallichiana.